Diversity, distribution, and ecology of the genus Hyalella Smith, 1874 (Crustacea: Amphipoda: Hyalellidae) in the Puna and the Altos Andes ecoregions of Argentina - Guillermo E. Hankel; Á. Verónica Isa Miranda; Carolina Nieto (Ecología Austral, 2023)
We studied the diversity, distribution and ecology of Hyalella (a genus endemic to America that lives over a wide range of geographical altitudes) in 44 peatlands of the Puna and the Altos Andes ecoregions, in the NW of Argentina, mostly placed in the provinces of Salta and Catamarca. Our aim is to deepen our understanding of the distribution and ecology of these freshwater crustaceans in both ecoregions. Field collection was made between 2013 and 2017, and ecogeographical variables were also recorded. The crustaceans were identified by dissections under a microscope. We estimated biodiversity indices and made Whittaker curves to compare diversity between both ecoregions. We made correlations between Hyalella abundance and 11 ecogeographic variables. A principal components analysis was made to study relationships among each peatland and eco-geographical variables. A total of 6548 individuals, distributed among 4 species and 11 morphospecies, were collected. Diversity in the Puna was higher than in the Altos Andes, but was low in each individual peatland. Hyalella fatimae was the most abundant species in both ecoregions. The PCA revealed that altitude, rainfall, temperature, electrical conductivity and total dissolved solids were key variables that characterized the peatlands. The abundance of Hyalella was negatively correlated with altitude and annual mean rainfall, and positively correlated with the mean minimum temperature of the coldest month. Hyalella proved to be an important component of macroinvertebrates assemblages in these environments, capable of generating a species complex and endemism, as reported for other regions of South America. The peatlands are important wetlands in the arid region of the Puna and the Altos Andes, and deserve more attention in the present context of being threatened by climatic change and the advance of economic activities.